IDENTITAS KELOMPOK PENGGUNA MOTOR YAMAHA RX KING DI KOTA MANADO - Saban, Aksul (Universitas Sam Ratulangi, 2015)
As human beings social and cultural, mutually need each other in a positive thing. Cultural differences have the identity of each suit character and tradition on a particular society. The traits that have become identity it is attached to a lifetime concomitant her life. Who shown actual not separated from social group that same culture . The rise of the user groups motorcycle Yamaha RX King in large cities describe that it is loved by many observers with various backgrounds. On the other hand society sometimes have a negative view of users against motor group, they consider the group less work, disrespectful in dress, robbed, scrappy and various other negative image indicated. Whereas those who views this negative not yet have an in-depth group activities motorcycle Yamaha RX King users. Started from exchange information in between users of motor Yamaha RX King in Kota Manado, then formed a group that does not reflect individual ego, but more form assembled brotherhood of a group in order to strengthen the relationship between fellow fans. Social solidarity that develops in this group, then becomes the pattern lifestyles and solidarity in the group. Those who are already exist and do good for the activities of government programs and other social activities . Keywords: motorcycle,Â identity, solidarity